Extending scientific workflows for managing hypotheses and models - Gonçalves, Bernardo; Porto, Fabio; Moura, Ana Maria de C. (Anais do Brazilian e-Science Workshop (BreSci), 2012)
Support for in-silico scientific exploration has been focusing on the research experimental phase. Nevertheless, there is valuable information associated to the research endeavor that has been left out of reach of the eScience environment and is mostly kept by scientists tacitly or in unstructured forms in their desktop environment. It concerns a description of the observed phenomenon, the conceptual formulation of scientific hypotheses as tentative explanations for it, as well as the models developed to encode these hypotheses. In this paper, we propose to extend scientific workflows in order to include such entities as data elements in the eScience environment, enabling then for their semantic management. These elements are integrated in a three-layered architecture which is illustrated in a case study in the modeling and simulation of the human cardiovascular system.